G120 Paediatric eating disorders: Management in a district general hospital. (24th May 2017) - Thaxter, D; Wadey, L
Abstract : ICD10 defines eating disorders (ED) as a 'broad group of psychological disorders with abnormal eating behaviours leading to physiological effects from overeating or insufficient food intake'. Anorexia nervosa (AN) is common, affecting one in every 250 women during their life. Bulimia nervosa (BN) is up to 5 times more prevalent, but neither are benign. The all-cause mortality of AN is 9.6%. Aims: Inpatient admission of paediatric ED patients can be a difficult experience, often leading to prolonged stays and generating conflict. We designed this audit to assess departmental compliance with national guidelines. We aimed to make recommendations for quality improvement and to answer the question: is inpatient management of low BMI effective? Methods: NICE Clinical Guideline 9 recommends weekly weight gain of 0.5–1kg for medical management of low body mass index (BMI). We inspected the admission records to identify patients for retrospective data collection. Our population included under18's admitted to the Paediatric Inpatient Ward with a formal or suspected diagnosis of ED as a primary diagnosis during the period 1 April 15 – 1 April 16. We designed a 12-part checklist drawn from NICE CG9 and our local guideline to evaluate our local practice. Results: 13 patients were selected, but 4 were excluded due to medical conditions contributing to ED. The mean age of the cohort was 15 years 9 months old. Average length of stay was 15.6 days, ranging from 1 to 63 days. 4 patients were admitted for re-feeding, 4 for physical illness and 1 for electrolyte disturbance. 5 patients were managed for low BMI with mean weekly weight gain of 0.15 kg. Family involvement in care was 88.9%, while 11.1% of patients had an admission planning meeting. One-to-one supervision was required in 55.6% of cases. Conclusion: Inpatient management of paediatric ED is an area for quality improvement. While medical measures are often done well, multi-disciplinary and admission planning measures were done poorly. The key metric of mean weekly weight gain falls short of NICE guidance, suggesting inpatient management of low BMI is not as effective as it should be.